ZwischenInnovation: Actor-Network Theory through Temporary Use in Bremen - Chang, Robin (AESOP, 2015)
The Actor-Network Theory (ANT) is born out of a discipline that is far beyond the spatial and theoretical borders typically associated with Planning. Since the theory's inception in the mid-1980s, ANT has been debated and ultimately shared across technical and social disciplines because of its concepts transferability. Despite its origins, it is hailed as a re-definitive, richer, active, transcendental idea and perhaps useful tool for urban studies including planning theory and practice. As a means of exploring how ANT can add value to planning by bridging theory and practice, this paper introduces and deploys ANT in the temporary use case study of Plantage 9 in the German city of Bremen, Hansestadt Brem to highlight potential contributions to planning. Practitioners use various forms of temporary strategic and tactical instruments for urban regeneration. Opportunities for affordable and acceptable experimentalism presented by temporary use activate urban regeneration and development. Temporary Use sets a background of shifting stability ideal for Problematisation and sets ANT in action. Research in this area is key to furthering the epistemological development of ANT in urban studies, and rooting the concept in planning theory and practice. As a theory that outlines methodology, ANT is a hybrid concept new to planning that lends itself as a heuristic benefit. The contributions of this research would help question and understand the processes, roles and competencies of an emerging and performative planning addressing urban decline.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015
Keywords: Actor-Network Theory; Urban Studies; Temporary Use; Performative Planning